PENGARUH SOCIAL MEDIA MARKETING DAN BRAND AWARENESS TERHADAP BRAND LOYALTY DENGAN VALUE CONSCIOUSNESS DAN BRAND LOVE SEBAGAI VARIABEL INTERVENING - Zhafira Utami Marhaban; I Made Bayu Dirgantara (Jurnal Akuntansi dan Pajak, 2023)
This study aims to examine the effect of value consciousness and brand love which is influenced by social media marketing and brand awareness on brand loyalty. Sampling was used using a purposive sampling technique, the total sample used was 254 respondents who are Shopee consumers who have made purchases at Shopee at least twice and who have more than one marketplace account. The data analysis technique used in this research is using SEM (structural equation model) analysis with the AMOS program, and data collection techniques using a questionnaire. The results show that social media marketing has a positive effect on value consciousness, value consciousness has a positive effect on brand loyalty, brand awareness has a positive effect on brand love, value consciousness has a positive effect on brand love, and brand love has no effect on brand loyalty. Keywords : social media marketing and brand awareness, value consciousness and brand love, brand loyalty